The Role of Botulinum Toxin A Neuromodulator in the Management of Synkinesis in Facial Palsy - Yener, Asalet; Acharya, Vikas; Andrews, Peter; Meller, Catherine; Shamil, Eamon (Facial Plastic Surgery, 2024)
Facial palsy describes the denervation of the facial nerve leading to difficulty in facial animation and expression. Facial synkinesis is the result of complex pathological nerve regeneration following damage to the facial nerve axons. Synkinesis in facial palsy can be managed using facial neuromuscular rehabilitation, botulinum toxin neuromodulators, and surgical treatment options. Botulinum toxin A can be used as an adjunct to other treatment options to manage synkinesis. This article will explore the role of botulinum toxin A in the management of synkinesis in facial palsy including the clinical assessment, injection location (muscles targeted), dosages, treatment interval, and long-term results. It will also include surgical management options.
Keywords: botulinum toxin; facial palsy; facial synkinesis; neuromodulator; management of synkinesis